High-dose chemotherapy and autologous haematopoietic stem-cell transplantation in older, fit patients with primary diffuse large B-cell CNS lymphoma (MARTA): a single-arm, phase 2 trial - Schorb, Elisabeth; Isbell, Lisa Kristina; Kerkhoff, Andrea; Mathas, Stephan; Braulke, Friederike; Egerer, Gerlinde; Röth, Alexander; Schliffke, Simon; Borchmann, Peter; Brunnberg, Uta; Kroschinsky, Frank; Möhle, Robert; et al. (The lancet. Haematology, 2024)
Background - Available treatments for older patients with primary diffuse large B-cell CNS lymphoma (PCNSL) offer progression-free survival of up to 16 months. We aimed to investigate an intensified treatment of high-dose chemotherapy and autologous haematopoietic stem-cell transplantation (HSCT) in older patients with PCNSL. - Methods - MARTA was a prospective, single-arm, phase 2 study done at 15 research hospitals in Germany. Patients aged 65 years or older with newly diagnosed, untreated PCNSL were enrolled if they had an Eastern Cooperative Oncology Group performance status of 0-2 and were fit for high-dose chemotherapy and autologous HSCT. Induction treatment consisted of two 21-day cycles of high-dose intravenous methotrexate 3·5 g/m2 (day 1), intravenous cytarabine 2 g/m2 twice daily (days 2 and 3), and intravenous rituximab 375 mg/m2 (days 0 and 4) followed by high-dose chemotherapy with intravenous rituximab 375 mg/m2 (day -8), intravenous busulfan 3·2 mg/kg (days -7 and -6), and intravenous thiotepa 5 mg/kg (days -5 and -4) plus autologous HSCT. The primary endpoint was progression-free survival at 12 months in all patients who met eligibility criteria and started treatment. The study was registered with the German clinical trial registry, DRKS00011932, and recruitment is complete. - Findings - Between Nov 28, 2017, and Sept 16, 2020, 54 patients started induction treatment and 51 were included in the full analysis set. Median age was 71 years (IQR 68-75); 27 (53%) patients were female and 24 (47%) were male. At a median follow-up of 23·0 months (IQR 16·8-37·4), 23 (45%) of 51 patients progressed, relapsed, or died. 12-month progression-free survival was 58·8% (80% CI 48·9-68·2; 95% CI 44·1-70·9). During induction treatment, the most common grade 3-5 toxicities were thrombocytopenia and leukopenia (each in 52 [96%] of 54 patients). During high-dose chemotherapy and autologous HSCT, the most common grade 3-5 toxicity was leukopenia (37 [100%] of 37 patients). Treatment-related deaths were reported in three (6%) of 54 patients, all due to infectious complications. - Interpretation - Although the primary efficacy threshold was not met, short induction followed by high-dose chemotherapy and autologous HSCT is active in selected older patients with PCNSL and could serve as a benchmark for comparative trials. - Funding - Else Kröner-Fresenius Foundation, Riemser Pharma, and Medical Center—University of Freiburg.
Online verfügbar 29 January 2024, Version des Artikels 27 February 2024
Gesehen am 09.10.2024